Diabetes Self-Care Activities (Diet & Exercise) and Adherence to Treatment: A Hospital –Based Study among Diabetic Male Patients in Taif, Saudi Arabia - Abubaker Ibrahim Elbur (Journal of Pharmacy and Nutrition Sciences, 2014)
Diabetes mellitus is a complex disorder that requires constant adherence to certain lifestyle measures and medication to achieve good glycaemic control. The main aim of this study was to measure adherence to self- care practices (diet, exercise and medication) among diabetic patients and to identify predicators of adherence. A hospital-based study was conducted in King Abdul Aziz Specialized Hospital, Taif, KSA during June – October 2013. Convenient method of sampling was adopted, whereby all adult (> 18 years) male diabetic patients were recruited. Data was collected through face-to-face interview method using structured questionnaire. Data was processed using the software Statistical Package for Social Science (SPSS) (Version 21). Overall 378 patients were eligible; 191 (50.5%) > 50 years old and nearly two third had secondary or university education. Overweight and obese patients constituted more than two third of the respondents. Generally adherence to diet, exercise was found to be low. Multivariate analysis showed that only presence of other diseases adjusted OR 2.8 (1.3-6.0), P = 0.011 and marital status adjusted OR 3.4 (1.0-11.7), P = 0.049 were found to be significantly associated with adherence to diet.Patients’ age was the only predicator for patients’ commitment to practicing exercise adjusted OR 4.7(1.3-17.8), P = 0.020). Non adherence to medication was found to 80.6 % (n=305). In conclusion non-adherence to the studied self-care practices was suboptimal. Proper and continuous health education accompanied with patients’ motivation may improve patients’ adherence.